Governança corporativa e o desempenho das empresas de construção civil listadas na BM&FBovespa - Santos, Adriano Lentz (Universidade do Vale do Rio dos Sinos, 2013)
The Corporate Governance (CG) theme has been subject of ongoing research in academic and professional areas. Corporate Governance can be defined as a system by organizations are driven, monitored and encouraged, involving relationships between its Owners, Management Board, Directors, control agencies and other stakeholders. An effective CG is considered an important business tool for companies' access to stock options. Based in these assumptions and the researcher interest in the Brazilian construction sector, this paper seeks to analyze the degree of evolution of Corporate Governance of Brazilian companies traded in this sector listed on the BM&FBovespa. This research was descriptive-oriented. Initially, it was identified the main indicator variables about level of governance established in the literature. The following variable were analyzed: the degree of independence of directors (INDEP), segregation or not of duties between the Presidency, Executive Presidency and membership on the Board of Directors (SC), number of Board members (TOT), the percentage of shares outstanding (FREE FLOAT), and attendance of differentiate level of CG by some companies of the BM&FBovespa. The results presented different situations. Almost all companies belong to different segment of governance; at the time, in most companies the CEO also attends the Board of Directors. Finally, it was verified how the five variables influencing the level of profitability of company stock and the same ROE. The results were not conclusive in this regard, with one significant variable, INDEP, however, this is presented with opposite sign than expected.
Keywords: Governança corporativa; Boas práticas; Construção civil; Desempenho; Corporate governance; Good practice; Construction; Performance; ACCNPQ::Ciências Sociais Aplicadas::Administração